(3JGQjN GdeYde hWjhWs - (3GdMSjf Hf ESeGYjd GdHLdj, hWjhWs ((3YHO Gddg gGOi MfHdi GdMcei s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdNdb CLeYjf CeG HYO abO SCdfi HYV GdGNhGf Cf GLeY cJGHkG dWjakG ai efGbH GdUGdMjf ef eTGjN SgGe s
(3BNQgG (B:s
(3fbd Edi QMeI Gddg JYGdi GdabjI GdCLd GdChd TQa GdOjf CHh GdbGSe Hf eMeO Hf YKeGf Hf CHj HcQ GdMcei s
(3hgh cJGH ai JGQjN hefGbH hCfSGH eTGjN (B" (3SgGe (B" (3ef VhGMi UfYGA HGdjefs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs